Presbyvestibulopathy, Comorbidities, and Perception of Disability: A Cross-Sectional Study - Soto-Varela, Andrés; Rossi-Izquierdo, Marcos; del-Río-Valeiras, María; Vaamonde-Sánchez-Andrade, Isabel; Faraldo-García, Ana; Lirola-Delgado, Antonio; Santos-Pérez, Sofía (Frontiers in Neurology, 2020)
Objective. To assess the perception of disability in patients with presbyvestibulopathy and to determine the factors (demographic, balance test scores, and comorbidities) that determine higher levels of disability. Material and Methods. This was a cross-sectional study conducted in a tertiary university hospital. There were 103 patients who fulfilled the diagnostic criteria for presbyvestibulopathy and were included. Dizziness Handicap Inventory (DHI) score was the main variable used to quantify disability. Influence on DHI score, sex, age, time of evolution, equilibriometric parameters (posturographic scores and timed up and go test), history of falls, comorbidities (high blood pressure, diabetes, and dyslipidemia), psychotropic drug use, tobacco or alcohol use, living environment (urban or rural), and active lifestyle were analyzed. Results. Most of the DHI scores showed a moderate (46 patients, 44,7 %) or severe (39 participants, 37,9 %) handicap. DHI scores were higher in women (59.8 vs 36.1, p<0.001), patients with obesity (58.92 vs 48.68; p=0.019), benzodiazepine (59.9 vs 49.1, p=0.008) or other psychotropic drug (60.7 vs 49.2, p=0.017) users, and fallers (57.1 vs 47.3, p=0.048). There was also a significant positive correlation between DHI score, time (Rho coefficient: 0.371, p<0.001), and steps (Rho coefficient: 0.284, p=0.004) used in the TUG and with the short FES-I questionnaire (a shortened version of the Falls Efficacy Scale-International) score (Rho coefficient: 0.695, p<0.001). DHI scores were lower in alcohol consumers than in non-drinkers (46.6 vs 56, p=0.048). No significant correlation was found between DHI scores and age, time of evolution, posturographic scores, comorbidities, environment (rural or urban), or active lifestyle. Conclusion. Most patients with presbyvestibulopathy show an important subjective perception of disability in relation to their symptoms. This perception is substantially higher in women than in men. The most influential factors are difficulties in walking, fear of falling, and obesity.